Endoscopic ultrasound as a reliable tool for assessment of pancreatic adenocarcinoma treatment: Example of in situ gene therapy - Buscail, Louis; Culetto, Adrian; Mokhrane, Fatima-Zhora; Napoléon, Bertrand; Meyrignac, Olivier; Molinier, Baptiste; Lebrin, Marine; Bournet, Barbara; Bérard, Emilie; Canivet, Cindy (Endoscopy International Open, 2022)
Background and study aims In pancreatic cancer, the antitumor effect can only be assessed by means of a computed tomography (CT) scan using RECIST (Response Evaluation Criteria in Solid Tumours) criteria. The aim of this study was to assess the intra-observer and interobserver agreement of endoscopic ultrasound (EUS) imaging in assessing tumor volume in primary pancreatic cancer.Patients and methods During a Phase 1 gene therapy trial, 21 patients had EUS before the first and second EUS-guided in situ gene therapy injections. All anonymized EUS files were then randomly distributed to three gastroenterologists/endosonographers and three radiologists (blind status). The largest tumor diameter was measured and the intraclass correlation coefficient (ICC) was determined.Results Intra-observer and interobserver agreements were good to excellent, regardless of operator experience (junior versus senior member of staff) (ICC: 0.65 to 0.84). A comparison of pretreatment and post-treatment measurements by the investigators highlighted a significant antitumor effect (–11 %; P = 0.0098), similar to that obtained during the generic protocol (–10 %; P = 0.0045).Conclusions Interobserver agreement regarding primary pancreatic adenocarcinoma measurements appears good to excellent, thus paving the way for the future inclusion of EUS assessments, particularly in trials assessing local therapies for pancreatic tumors.